Educational autopsy: An innovative structured debrief for residency didactic teaching. Issue 3 (28th June 2021) - Griffith, Max; Brown, Charles; Haas, Mary R. C.; Huang, Robert D.; Hopson, Laura R.
Abstract: Background: Educational autopsy (EA) is an innovative technique designed to improve the quality of feedback provided to conference presenters. In response to survey fatigue and suboptimal feedback from online evaluations, this postlecture group debrief was adapted to emergency medicine residency didactics, with a goal of collecting timely, specific, and balanced feedback for presenters. Other aims include encouraging participants to think critically about educational methods and providing presenters with formal feedback for a portfolio or promotion packet. It was hypothesized that EA provides more specific and actionable feedback than traditional online evaluations deployed individually to conference attendees. Methods: The authors analyzed 4 months of evaluations pre‐ and postimplementation of EA. Rate of completion, presence of comments, and types of comments were compared. Comments were coded as specific, nonspecific, and unrelated/unclear. Specific comments were further categorized as about audiovisual presentation design, speaker presentation style, and educational methods of the session. Results: A total of 46 of 65 (71%) preimplementation presentations eligible for evaluation received comments through traditional online evaluations. A total of 44 of 75 (59%) eligible postimplementation presentations generated comments via EA. Among presentations that received comments, none received nonspecific comments via EA, compared to 46% of lectures through traditional evaluations. EA generated specific comments for more presentations regarding presentation design (91% vs. 63%), presentation style (66% vs. 24%), and educational methods (48% vs. 28%). EA produced no unclear comments; traditional evaluations resulted in unclear comments for 15% of lectures. Conclusions: EA generated more specific feedback for residency conference presenters, although there were a number of sessions not evaluated by EA. Although this limited analysis suggested that EA produced higher‐quality presenter feedback, it also showed a drop‐off in the proportion of didactic sessions that received narrative feedback.